The Experience of Facebook by Self- Confessed Facebook Addicts: Characteristics, Consumption Habits and Identity. - Ali, Liah Kamal (2010)
Abstract The study examined the consumption habits of self- confessed Facebook addicts, especially those from the Middle East. The research firstly involved an online survey, which 124 participants responded to. The participants were partly members who had joined a Facebook group called “I am a Facebook Addict” created especially for this study, as well as groups and fan pages with similar titles. The study then went on to involve six interviews with Middle Eastern interviewees who had all joined the group and answered the survey. The survey found that the majority of self- confessed Facebook addicts were between the ages of 20- 29 years old, and accessed Facebook “several times a day” according to the survey. In addition, females seemed to be more addicted than males were as the number of female self- confessed addicts were almost double the male participants. As far as activities most performed went, “reading news feeds” was clearly the most frequently performed, while joining and taking part in groups, and posting and reading notes, were the least performed. Participants were also found to provide profile information to other users in order to primarily express themselves. Another interesting finding was that in comparison to a study by Pempek et al. (2009) of regular Facebook users, the results were almost identical in terms of activities mostly performed and characteristics of the participants. However, the frequency of using Facebook was higher for self- confessed addicts than non- addicts, as the addicts accessed it “several times a day” while non- addicts “a few times a day”. Finally, most of the participants who had mobile phones believed that mobile phone access did increase their use of Facebook, as was shown in the interviews as well. The interview stage also revealed other findings such as the reason for using Facebook excessively, and which was found to be in order to communicate with friends and keep in touch with them. This was followed by the participants filling in their time with Facebook when bored. Furthermore, it was revealed that that the participants viewed themselves as addicts for reasons unlike those defined in previous literature, since the participants defined it due to their excessive use of Facebook. They also did not suffer from any symptoms such as loss of control, withdrawal symptoms, suffering from other addictions, or being shy and wanting to escape reality through the use of the Internet, or allowing the addiction to have negative effects on their lives. They did not access other social networks frequently and did not suffer from any other addictions either. In fact, it seemed that Facebook was actually aiding the participants in becoming more sociable, as it eliminated boundaries, which, in the past, had prevented the participants from communicating with their friends as frequently, as they admitted that all their friends now had Facebook, and that was also why they had an account. Additionally, it was found that participants did express their idenities implicitly through Facebook, by adding photos, “liking pages”, and updating their “current status”. There was no general finding in regards to Facebook use being triggered by a certain setting, such as the location of the user at the time of use, as 4 of the interviewees had mobile access and so their Facebook use had no restrictions. One participant related using Facebook mostly while at home, while the other wished to use Facebook wherever they were, but did not have this kind of access to it. Finally, the issue of Facebook groups and fan pages was examined, and it was found that Facebook groups were not as popular as Fan pages anymore, and that fan pages were more effective for businesses to use in order to better communicate and understand consumers.